Microstructure evolution and mechanical properties of TiB/Ti6Al4V composites based on selective laser melting - Huang X.; Zhu Y.-T.; Huang W.-D.; Qin S.-S.; Wang L. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this paper, Ti6Al4V+3 wt.% TiB2 composite powder was used as a raw material to synthesize TiB whiskers in situ and prepare composites reinforced with TiB/Ti6Al4V whiskers by selective laser melting (SLM). The effects of process parameters on the properties of TiB/Ti6Al4V samples were systematically studied. The evolution of the microstructure, including the formation and regulation of whiskers, and the effects on mechanical properties were discussed. The results showed that during the SLM process, adjusting the energy density effectively inhibited cracking in the TiB/Ti6Al4V samples. The TiB2 particles acted as nucleation centers to significantly refine the grains during processing and reacted with elemental Ti to form a needle-like TiB network at the grain boundaries, which strengthened the whiskers. Additionally, TiB played a role in dispersion strengthening. Compared with Ti6Al4V, the microhardness of TiB/Ti6Al4V was 430.6±11.45 HV, an increase of 27.9%, and the wear volume of the sample was 0.85×10-3 mm3, a decrease of 62.64%.